BDNF Val66Met polymorphism alters food intake and hypothalamic BDNF expression in mice. Issue 12 (19th May 2020) - Ieraci, Alessandro; Barbieri, Silvia S.; Macchi, Chiara; Amadio, Patrizia; Sandrini, Leonardo; Magni, Paolo; Popoli, Maurizio; Ruscica, Massimiliano
Abstract: Obesity, a rising public health burden, is a multifactorial disease with an increased risk for patients to develop several pathological conditions including type 2 diabetes mellitus, hypertension, and cardiovascular disease. Increasing evidence suggests a relationship between the human brain‐derived neurotrophic factor (BDNF) Val66Met single‐nucleotide polymorphism (SNP) and obesity, although the underlying mechanisms of this connection are still not completely understood. In the present study, we found that homozygous knock‐in BDNF Met/Met mice were overweight and hyperphagic compared to wildtype BDNF Val/Val mice. Increased food intake was associated with reduction of total BDNF and BDNF1, BDNF4 and BDNF6 transcripts in the hypothalamus of BDNF Met/Met mice. In contrast, in the white adipose tissue total BDNF and Glut4 expression levels were augmented, while sirtuin 1 and leptin receptor (Ob‐R) expression levels were reduced in BDNF Met/Met mice. Moreover, plasmatic leptin levels were decreased in BDNF Met/Met mice. However, BDNF Val/Val and BDNF Met/Met mice showed a similar response to the insulin tolerance test and glucose tolerance test. Altogether, these results suggest that BDNF Val66Met SNP strongly contributes to adipose tissue pathophysiology, resulting in reduced circulating leptin levels and hypothalamic expression of BDNF, which, in turn, promote increased food intake and overweight in BDNF Met/Met mice. Abstract : We described that homozygous knock‐in BDNF Met/Met mice were overweight and hyperphagic compared to wildtype BDNF Val/Val mice. These alterations were associated with gene expression changes of BDNF, SIRT1, and ObR in the hypothalamus and white adipose tissue. Moreover, plasmatic leptin levels were decreased in BDNF Met/Met mice.